PENGARUH MOTIVASI DAN KOMPETENSI TERHADAP KINERJA PEGAWAI BADAN PENGAWASAN KEUANGAN DAN PEMBANGUNAN (BPKP) PERWAKILAN SUMATERA BARAT - Budi Yanti (Ensiklopedia of Journal, 2022)
Abstract: The purpose of this study was to determine and analyze the effect of motivation and competence on employee performance at BPKP Representative West Sumatra. The method used in this research is descriptive quantitative. The population in this study were 127 employees of BPKP Representatives of West Sumatra and the sample in this study amounted to 56 respondents. While the data analysis technique used in this research is multiple linear regression, t test, F test, and coefficient of determination. Based on multiple linear regression analysis Y = 4.058 + 0.516X1 + 0.345X2 + e. The t-test with the results of the motivational variable test has a value of tcount > ttable that is (3.975 > 1.674) and significant (0.000 < 0.05), it can be concluded that Ho is rejected and H1 is accepted while the competency variable test has a value of tcount > ttable that is (4,298 > 1.674) and significant (0.000 < 0.05), it can be concluded that Ho is rejected and H2 is accepted. F test with the results of Fcount > Ftable (38.371 > 3.17) and a significant level (0.000 < 0.05), then Ho is rejected and H3 is accepted. While the value of the coefficient of determination produced is 0.576. That is, the coefficient of determination is known that the Adjusted R-square value is 57.6%, the remaining 42.4% is explained by other variables not discussed in this study.Keywords: Motivation, Competence and Employee Performance.